2017
DOI: 10.1111/imb.12295
|View full text |Cite
|
Sign up to set email alerts
|

Three odorant binding proteins may regulate the behavioural response of Chrysopa pallens to plant volatiles and the aphid alarm pheromone (E)‐β‐farnesene

Abstract: Artificial Chrysopa pallens release is a well‐known method for suppressing aphids, but it is difficult to establish lacewing populations in the field. Understanding the functions of C. pallens odorant‐binding proteins (CpalOBPs) and behavioural responses of C. pallens to plant volatiles and aphid alarm pheromone (E)‐ß‐farnesene has important implications for population establishment after lacewing release. Based on our previous study, five antennae‐enriched CpalOBPs were selected. Sequence alignment and phylog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 49 publications
2
25
0
Order By: Relevance
“…However, all the volatiles tested in this study showed a relatively weak binding affinity (Ki > 20 μM) to HparOBP49. Compensation effects may exist between HparOBP20 and HparOBP49, as observed for Cnaphalocrocis medinalis OBP2 and OBP3 ( Sun et al, 2016 ), and Chrysopa pallens OBP3, -6 and -10 ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 86%
“…However, all the volatiles tested in this study showed a relatively weak binding affinity (Ki > 20 μM) to HparOBP49. Compensation effects may exist between HparOBP20 and HparOBP49, as observed for Cnaphalocrocis medinalis OBP2 and OBP3 ( Sun et al, 2016 ), and Chrysopa pallens OBP3, -6 and -10 ( Li et al, 2017 ).…”
Section: Discussionmentioning
confidence: 86%
“…Cedrene had a specific relation with antimicrobial, Which has always been considered as the derived compounds of essential oils . The intensity of cedrene from UF eggs was much higher than that from Fd eggs, which could be interpreted as the faster emission rate in UF eggs and the odorant‐binding proteins in eggshell could selectively absorb and release odors …”
Section: Resultsmentioning
confidence: 99%
“…32 The intensity of cedrene from UF eggs was much higher than that from Fd eggs, which could be interpreted as the faster emission rate in UF eggs and the odorant-binding proteins in eggshell could selectively absorb and release odors. 33 In Fd and UF eggs, significant changes in seven protein spots were identified at an early stage of incubation, and the intensity of 24th spot (ovoinhibitor) was significantly changed on day 0 of incubation. 18 In Fd and UF eggs, more than 40 protein spots significantly changed in eggshell membrane (ESM) at day 0 of incubation.…”
Section: Differences Of Vocs From Uf and Fd Eggsmentioning
confidence: 94%
“…Chrysopa pallens (Li et al 2017). However, previous electroantennogram results showed that the antennae of Chrysoperla carnea are highly sensitive to EBF (Zhu et al 1999), which can support the increased abundance of lacewings observed in EBF treatment compared to Control.…”
Section: Discussionmentioning
confidence: 87%